Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan dan Sikap Siswa SMP Dharma Pancasila Tentang Manajemen Kesehatan Menstruasi - Nur Asnah Sitohang; Cut Adeya Adella (Jurnal Riset Hesti Medan, 2019)
Menstrual Hygiene Management (MHM) is the management of hygiene and health when women experience menstruation. The main problem in adolescents related to menstruation is the lack of knowledge about MSM and poor water sanitation. Many girls don't have the right understanding that menstruation is a normal biological process. Community service aims to improve students' knowledge and attitudes about menstrual health management. The method used is socializing; identify the state of menstrual health service facilities in schools: bathrooms, water, information; carry out bathroom renovations; provide educational media about menstrual health management in the form of posters, videos, leaflets, modules and flip sheets. Pre-test and post-test aims to identify students' knowledge and attitudes about menstrual health management. Analysis of the data used is the dependent t test. The knowledge of students before being given health education majority was in the sufficient category and thereafter increased to good. Likewise, students' attitudes increase to be positive. The statistical test results obtained mean difference of 7.72 and P Value = 0.001, it can be concluded that there is a significant effect of health education on knowledge. For attitudes the mean difference is 1.62 and the P value  = 0.001, it can be concluded that there is a significant influence on health education on student attitudes. Therefore it is suggested to the school to include this topic in the subject matter. So students can apply it early and their reproductive health can be maintained.